Woody Allen: Camus’s Existentialism as Comedy - Lauder, Robert E. (Philosophy & theology, 1988)
Critics’ praise of Woody Allen as an artist is increasing. No other comedian includes within his humour so many references to God. Philosophers interested in contemporary culture should take Allen’s comedy seriously. Accepting Albert Camus’s vision of reality, Allen has been artistically handling the absurdity of reality by use of humour. Through comedies, Allen’s films deal with important questions. His finest film may contain an argument for God.